Quality and nutraceutical properties of mango fruit: influence of cultivar and biological age assessed by Time‐resolved Reflectance Spectroscopy - Maristella Vanoli; Maurizio Grassi; Lorenzo Spinelli; Alessandro Torricelli; Anna Rizzolo (Advances in Horticultural Science, 2018)
The content and composition of the main antioxidants in the pulp of mangoes depend also on cultivar and maturity degree, the latter being non-destructively evaluated by the absorption coefficient measured by Time-resolved Reflectance Spectroscopy (TRS) at 540 nm (µa540). Aiming at evaluating the levels of antioxidants [carotenoids (CAR), phenols (TPC), ascorbic acid (AA)] and antioxidant capacity (TAC) in relation to µa540 maturity class, selected ‘Haden’ and ‘Palmer’ mangoes were measured for µa540 by TRS, classified based on µa540 value as less (LeM), medium (MeM) and more (MoM) mature and analyzed for pulp firmness, pulp color (a*, h°, Yellowness Index), CAR (total and composition by HPLC-DAD), TPC, AA and TAC. ‘Palmer’ fruit had higher TPC, AA and TAC than ‘Haden’ mangoes. On average MoM fruit showed higher TPC, total CAR, total all‐trans‐violaxanthin esters and all‐trans‐β‐carotene than MeM and LeM fruit. LeM fruit did not have compounds belonging to the 9‐cis‐violaxanthin group, while cis‐β‐cryptoxanthin was approx. 19% of total carotenoids. In MoM mangoes the main carotenoid was all‐trans‐β-carotene (53%), followed by total all‐trans‐violaxanthin esters (30%), 9‐cis‐violaxanthin group (8%) and cis‐β‐cryptoxanthin (6%). The µa540 significantly correlated (r=0.78‐0.94) with total CAR, all‐trans‐β‐carotene, all‐trans‐violaxanthin no.3 (both cultivars), TPC, all‐trans‐violaxanthin no.1, no.2, no.6 (‘Haden’), and 9‐cis‐violaxanthin no.2, no.3 (‘Palmer’). Our results indicate that TRS is suitable to non-destructively measure the pulp color of mangoes and to sort fruit with different ripening degree and nutraceutical properties.